Adenoid Basal Carcinoma of Uterine Cervix: A Case Report - Selçuk, İlker; Öz, Murat; Sirvan, Levent; Güngör, Tayfun; Meydanlı, Mehmet Mutlu (Gynecology Obstetrics & Reproductive Medicine, 2016)
Adenoid basal carcinoma of uterine cervix is a very rare entity that has been reported less than 100 cases in the literature. Although the origin of the carcinoma is controversial; the multipotential basal cell layer of cervix is the believed part for tumor growth. A 54 years-old white postmenopausal woman was referred to our clinic with the complaint of postmenopausal bleeding. Her pelvic examination revealed a tumor lesion of 1.5cm on the ectocervix. Her cervical and endometrial biopsies revealed an epithelial carcinoma and we performed a radical hysterectomy with bilateral salpingo-oophorectomy and bilateral pelvic-paraaortic lymph node dissection. The final pathology result revealed adenoid basal carcinoma. Distinction of adenoid basal carcinoma from adenoid cystic carcinoma and other aggressive basaloid pathologies of cervix is important for the clinical management of patients since adenoid basal carcinoma is benign in behaviour despite being a carcinoma.